2022
DOI: 10.5812/fga-132085
|View full text |Cite
|
Sign up to set email alerts
|

Could the Increase in Fetal Movement Be a Sign of the Imminent Fetal Demise? A Case Report

Abstract: Background: Monitoring fetal movement is a simple and effective approach to assessing fetal well-being. Among other issues, the maternal perception of altered (not just reduced) fetal movements remains a complex issue. This study aimed to report a case of fetal demise following the increased fetal movements in the third trimester of pregnancy. Case Presentation: A 32-year-old woman in 34th week of her first pregnancy attended the emergency room while she had no chief complaint of fetal movement from the previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Regarding the maternal perception of fetal movements, some clinical data indicated that increased movements are associated with adverse perinatal outcomes [ 15 , 16 ]. But these data are currently insufficient and sparse [ 17 ]. In addition, there is no systematic review that evaluated the risk of adverse outcomes such as stillbirth among women reporting this symptom, and also, it is still unclear how to reduce the risk.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the maternal perception of fetal movements, some clinical data indicated that increased movements are associated with adverse perinatal outcomes [ 15 , 16 ]. But these data are currently insufficient and sparse [ 17 ]. In addition, there is no systematic review that evaluated the risk of adverse outcomes such as stillbirth among women reporting this symptom, and also, it is still unclear how to reduce the risk.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that medical interventions during the period of FM decrease may result in the delivery of a healthy, living baby [ 6 , 7 ]. In addition to reduced FM, excessive FM can be a risk factor contributing to stillbirth [ 8 ]. Therefore, early detection of risk factors and timely intervention can reduce the incidence of stillbirth by establishing prenatal FM detection.…”
Section: Introductionmentioning
confidence: 99%